Round Robin Tests on Nitrosamines Analysis in the Effluents of a CO2 Capture Pilot Plant. (January 2016) - Fraboulet, I.; Chahen, L.; Lestremau, F.; Grimstvedt, A.; Schallert, B.; Moeller, B.C.; Järvinen, E.
Abstract: Processes of post combustion CO2 capture using amine based solvents generate nitrogenous compounds. Among these products, carcinogenic nitrosamines are of great concern due the potential impacts on the environment and human health. Trace analysis of nitrosamines in simple matrices such as water is well described in standard methods[1] . However, measuring nitrosamines in CO2 capture processes emissions is much more challenging. Nitrosamines, formed to small concentrations as solvent degradation products, may indeed be present in solvent, wash waters, and atmospheric emissions which are more complicated to monitor. Within the FP7 OCTAVIUS project, 2 international round robins on the analysis of 9 nitrosamines in solvent matrices and the atmospheric emissions, from the EnBW CO2 capture pilot plant in Heilbronn (Germany) were organized. The first round robin test was performed on solvent matrices. The analytical methods of the laboratories involved were compared using synthetic spiked samples and liquid samples obtained from the pilot plant. The second round robin test was performed on atmospheric emissions collected using a sampling train with cold impingers filled in with sulphamic acid in water. Each laboratory was provided with two blind samples of the liquid mixture spiked at different levels of concentrations of nitrosamines.